The Role of Institutional Entrepreneur in Realizing Sustainable Tourism Development in Kelor Tourism Village - Muhamad Farhan; Peni Arianita Wardani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study is to analyze the role of institutional entrepreneurs in realizing sustainable tourism development in Kelor Tourism Village. This research uses a descriptive qualitative research method. There are three essential stages carried out in this research: First, the stage of searching for symptoms that appear or occur in the object of research. The second is identifying the relationship between one symptom and another in the investigated aspects. Third, the analysis and interpretation stage of identifying the relationship between the symptoms and the aspects investigated. This research was conducted in the Kelor Tourism Village, located in Kelor Hamlet, Bangunkerto Village, Turi District, Sleman Regency. Based on the results of research and analysis, it can be concluded that the interaction between actors in forming the Dewikadjar Tourism Awareness Group to become an innovative and sustainable institution is carried out continuously from the formation stage to management